2023
DOI: 10.1039/d3ta01025b
|View full text |Cite
|
Sign up to set email alerts
|

CO2heterogeneous hydrogenation to carbon-based fuels: recent key developments and perspectives

Abstract: The emission of a large amount of anthropogenic carbon dioxide leads to a series of detrimental effects, such as the destruction of the ecological environment. Heterogeneous catalytic hydrogenation of carbon...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 267 publications
(340 reference statements)
0
3
0
Order By: Relevance
“…In addition to Fe-based catalysts, the HZSM-5 zeolite is also critical for converting syngas to aromatics. , The HZSM-5 zeolite is responsible for converting lower olefins into aromatics via dehydrogenation, cyclization, aromatization, and alkylation. , The pore structure, morphology, and acidic properties determine the aromatization ability of a zeolite and the distribution of aromatic products. In recent years, a host of studies have been reported on the HZSM-5 zeolite. Table S1 compares the performances of various catalysts in syngas conversion to aromatics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Fe-based catalysts, the HZSM-5 zeolite is also critical for converting syngas to aromatics. , The HZSM-5 zeolite is responsible for converting lower olefins into aromatics via dehydrogenation, cyclization, aromatization, and alkylation. , The pore structure, morphology, and acidic properties determine the aromatization ability of a zeolite and the distribution of aromatic products. In recent years, a host of studies have been reported on the HZSM-5 zeolite. Table S1 compares the performances of various catalysts in syngas conversion to aromatics.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the conversion of CO 2 into high-value-added chemicals (such as methanol, ethanol, light hydrocarbons, gasoline range hydrocarbons, and aromatics) has attracted widespread attention [1][2][3]. To produce C 2+ chemical products from CO 2 hydrogenation, the direct CO 2 Fischer-Tropsch synthesis (CO 2 -FTS) process and the methanol intermediate route have been proven as two indispensable and effective routes [4][5][6][7][8][9]. The methanol intermediate route involves methanol synthesis from CO 2 and H 2 by single or multiple metal-oxide catalysts and follows by using zeolites to catalyze methanol into dimethyl ether, light olefins, gasoline range hydrocarbons, light aromatics, etc.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, owing to the sluggish eight-electron-coupled proton transfer process, competitive H 2 evolution reaction (HER), as well as the relatively facile C–C coupling step towards C 2+ products, the activity and selectivity for CO 2 reduction to CH 4 using Cu-based electrocatalysts remain unsatisfactory. 4 To this end, several effective strategies, including control over the morphology, 5 size, 6 and crystallographic facets 7 and engineering of the electronic structure of active sites by introducing defect sites, 8 forming alloys, 9 and surface modifications, 10 have all been proposed to promote CH 4 production using Cu-based catalysts.…”
mentioning
confidence: 99%